Effective anti-inflammatory phenolic compounds from dandelion: identification and mechanistic insights using UHPLC-ESI-MS/MS, fluorescence quenching and anisotropy, molecular docking and dynamics simulation - Hui Zou; Tingting Ben; Ping Wu; Geoffrey I.N. Waterhouse; Yilun Chen (Food Science and Human Wellness)
This novel study identifies the effective anti-inflammatory phenolic compounds in dandelion and provides mechanistic insights into their interactions with receptor proteins (toll‐like receptor 4, TLR4; co‐receptor myeloid differentiation protein-2, MD-2) using UHPLC-ESI-MS/MS, lipopolysaccharide (LPS)-stimulated THP-1 cell line, fluorescence quenching and anisotropy, molecular docking (single ligand and multi-ligand docking) and molecular dynamics simulation. A 50 % aqueous methanol extract had a greater anti-inflammatory effect and higher chicoric acid content, compared with the 100 % water and 100 % methanol extracts. Chicoric acid, chlorogenic acid, methylophiopogonone A, caffeic acid, gallic acid monohydrate and 4'-O-demethylbroussonin A had relatively high binding energies and contents in all extracts. Chicoric acid competed with chlorogenic acid, 4'-O-demethylbroussonin A and quercetin for MD-2. Among dandelion’s phenolics, chicoric acid most effectively hindered TLR4-MD-2 complex formation, with a quenching constant of 0.62 × 106 L/mol for MD-2 or TLR4 at 320 K, and binding energies of –6.87 and –5.97 kcal/mol, respectively, for MD-2 and TLR4.